brModeloWeb: Ten Years of History and a New Extension for the Logical Design of NoSQL Databases - Souza Neto, Milton Bittencourt de; Mello, Ronaldo dos Santos (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais Estendidos do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2026.249398, 2026)
The brModelo initiative began in 2005 with the purpose of providing semiautomated solutions to assist Database modeling education. Supported by the UFSC Database Group, the initiative comprises a set of tools developed over these 21 years, of which brModeloWeb is the most recent. Available since 2016, brModeloWeb reaches 10 years of existence with more than half a million registered users from universities and professionals that adopt it for both educational and real-world database design. This paper celebrates the successful adoption of brModeloWeb and presents a new extension for NoSQL logical design, introduced in the latest release, along with performance improvements. A usability evaluation conducted during a workshop at the Brazilian Database School (ERBD 2026) indicated that the tool was well received.